A REVIEW OF SCIENTIFIC RESEARCH ON THE IMPLEMENTATION OF TRADITIONAL MEDICINE IN REHABILITATION Sladjana Arsic,1 Dragana Kljajic,2Marija Trajkov,2Stevan Jovanovic2 Mile Despotovic1 1*Sladjana Arsic, PhD, High Medical School of Professional Studies, Addre - Arsić, Sladjana D (PONS - medicinski časopis, 2018)
Traditional medicine (TM) is an expression used for a part of alternative medicine or medicine that is grounded on a folk knowledge.Regardless of the official position of the medicine, the use of methods of traditional medicine is constantly increasing, especially in the most developed countries.For example,70% of the population in Canada and 80% in Germany are using some form of alternative or complementary medicine.In traditional medicine, the emphasis is on balance or “harmony” in the body, since the body is associated with the earth and the cosmos which is very important for the healing process. There are contrary opinions that claim that TM is a huge collection of never proven theory.A new way of looking and interpreting of all the evidence and observations about the processes of sickness and healthis necessary for provingTM. There are enormous differences between TM and conventional medicine, both in the methods used for any kind of intervention and in the way doctors and healers are trained.It is also important to note that studies in the field of TM are using norms and standards used for research in conventional medicine, which means that they are not adapted to the basic characteristics of TM.Therefore, scientific and research work about the importance of the use of TM requires one continuous process in which participants from different frameworks, complete impartiality and in accordance with results from the obtained studies, make conclusions.The research results presented demonstrate the positive effects of the use of TM methods in rehabilitation. Key words: traditional medicine; alternative; complementary;